Ukrainian–Russian bilingualism in the war-affected migrant and refugee communities in Austria and Germany: a survey-based study on language attitudes - Warditz, Vladislava; Meir, Natalia (Frontiers in Psychology, 2024)
This paper provides an initial exploration of Ukrainian-Russian bilingualism in the context of the war-affected migration from Ukraine to Germany and Austria. While extensive research exists on various aspects of Ukrainian-Russian bilingualism in relation to Ukraine itself, thus far no studies have been conducted on this bilingualism in the diasporic context, i.e., as a language of the first and subsequential generations with a migrant background in Germany and Austria.To address this research gap, our paper examines the language attitudes of two respondent groups with a Ukrainian background in the two countries: migrants and refugees who left Ukraine after 2014 and those who left after Russia's invasion in February 2022. In the framework of a sociolinguistic survey, we describe their current attitudes regarding the use of Ukrainian and Russian, among others, in relation to the actual and intended use of the language(s) in the multilingual context of migration. The survey eliciting information on demographic information, language proficiency, language attitudes and language use was conducted on 406 Ukrainians in two host countries (Austria: n=103; Germany: n=306). First, we compared self-rated proficiency in Ukrainian and Russian as well as attitudes and use of these languages. Second, we applied a network modelling analysis to determine the nature of relationships between these variables. The results indicated that proficiency in Ukrainian and in Russian were the strongest nodes in the model affecting language use and language attitudes toward the respective languages.Our data analysis focused on the pragmatic and symbolic value of Russian and Ukrainian playing a crucial role in the language vitality in multilingual settings. The paper discusses the imbalanced correlation of the symbolic and pragmatic value of Ukrainian and Russian in the diasporic Ukrainian communities. While Ukrainian has gained a higher symbolic status, Russian maintains a better pragmatic one, despite its negative symbolic status. However, we anticipate that the increasing symbolic value of Ukrainian and the diminishing value of Russian will lead to an increase in the use of Ukrainian also in Russian-dominant bilingual groups of Ukrainian migrants and refugees, even as an insider-code in hermetic minority groups.